Loneliness and biological responses to acute stress in people with Type 2 diabetes - Hackett, Ruth A. (Psychophysiology, 2019)
Loneliness is linked with all‐cause mortality and coronary heart disease. Altered neuroendocrine and inflammatory responses to stress constitute potential pathways linking loneliness and ill‐health. Stress responsivity is modified in people with Type 2 diabetes, but it is unclear whether loneliness influences biological stress responses in this population. We assessed interleukin‐6 (IL‐6), interleukin‐1 receptor antagonist (IL‐1RA), monocyte chemoattractant protein‐1 (MCP‐1), and cortisol responses to acute stress in 135 people with Type 2 diabetes. Loneliness was measured used the Revised UCLA Loneliness Scale. Loneliness was inversely associated with cortisol output poststress (B = −4.429, p = 0.019) independent of age, sex, education, marital status, body mass index, and smoking. Lonelier individuals had raised MCP‐1 concentrations 75 min poststress independent of covariates (B = 0.713, p = 0.022). No associations between loneliness and IL‐6 or IL‐1RA concentrations were detected. These results suggest that loneliness is associated with disturbances in stress responsivity in people with diabetes, and the impact of loneliness on health in people with diabetes may be mediated in part through dysregulation of inflammatory and neuroendocrine systems. Future research is required to understand if such changes increase the risk of poorer outcomes in this population.